10x+6-8x=9x+12-8x-2

Simple and best practice solution for 10x+6-8x=9x+12-8x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10x+6-8x=9x+12-8x-2 equation:



10x+6-8x=9x+12-8x-2
We move all terms to the left:
10x+6-8x-(9x+12-8x-2)=0
We add all the numbers together, and all the variables
10x-8x-(x+10)+6=0
We add all the numbers together, and all the variables
2x-(x+10)+6=0
We get rid of parentheses
2x-x-10+6=0
We add all the numbers together, and all the variables
x-4=0
We move all terms containing x to the left, all other terms to the right
x=4

See similar equations:

| 6v-v=65 | | 2(1-3n)+5=-4(2n+1) | | 7x-3-3x=1 | | 6x=-16x | | –4.4(v−19)=13.2 | | 7f+8=22 | | 0.4x+0.6=0.6x-0.2 | | 6x-x=75 | | 4+9-3c+3c=13 | | 40=x20 | | −6(b+3)+6b=−6(−4b+3) | | -4-4t=8-10t | | 3(x=1)-2(3x+7) | | -3-7y=2+7-13 | | 5z+1=z | | 4x+2x+6=2(3x+2) | | 7x-3=30 | | 5s=4s+9 | | 6(t+2)=2t+28 | | -8f-5-2=9-10f | | 7x+56=8 | | (x+1)3+3=3(4+2x) | | 2t-1=3-6 | | y2−6y=0 | | 4.2(q−16.1)=–2.1 | | -4v-3=-10v-9 | | -7(y+3)=-2y+14 | | 12.25=0.75x | | 6-6v+5=-4-3v | | -2x-2=3×+1 | | 7w=-10=8w | | −6x+(−11)x+20=15+17 |

Equations solver categories